MARKETING RISKS AND STRATEGIES OF SMEs IN THE SECOND DISTRICT OF CAPIZ - Mary Grace, Boñales (IDEAS: Journal of Management & Technology, 2024)
The study was conducted to determine the level of marketing risks and the degree of marketingstrategy of 198 randomly selected small and medium enterprise in the second district of Capiz.The researcher utilized a descriptive-correlational research design. Random sampling wasemployed to determine the number of respondents per municipality. A validated and reliabilitytested researcher-made questionnaire was used to gather the needed data. Statistical toolsused to analyze and interpret data were frequency count, percentage, mean, Analysis ofVariance and Pearson-r. The findings of the study revealed that the level of marketing risk ofSMEs in the second district of Capiz as a whole was very high. Moreover, the degree ofmarketing strategies of SMEs as a whole was high. The result of the study found that there wasa significant difference in the level of marketing risk of SMEs in the second district of Capizwhen grouped according only to number of years in business operation. There was asignificant difference in the degree of marketing strategy of SMEs in the second district ofCapiz when grouped according only to type of business. Lastly, the level of marketing risk issignificant to the degree of marketing strategy of SMEs in the second district of Capiz